Distribution of the positive UPOINT domain in patients with chronic prostatitis or chronic pelvic pain syndrome: A multicenter observational study. Issue 5 (May 2022) - Ichihara, Koji; Takahashi, Satoshi; Hiyama, Yoshiki; Masumori, Naoya; Nagae, Hiroshi; Ito, Shin; Wada, Koichiro; Betsunoh, Hironori; Hamasuna, Ryoichi; Togo, Yoshikazu; Shigemura, Katsumi; Takeyama, Ko
Abstract: Objective: To determine the UPOINT-positive domain numbers and evaluate the significance of the sexual dysfunction domain in patients with chronic prostatitis or chronic pelvic pain (CP/CPPS) in Japan. Methods: A total of 58 patients with CP/CPPS with moderate or greater symptoms were included. Symptom severity was determined by > 14 on the chronic prostatitis symptom index (CPSI). The main outcome was to confirm the number and distribution of the positive UPOINT domains in this group. As secondary outcomes, the correlation between positive domain numbers and CPSI scores was evaluated. We also examined whether the sexual dysfunction subdomain, as determined by the five-item international index of erectile function, could improve the correlation with symptom severity. Results: The mean age was 48.6 ± 15.4 years, CPSI score 24.3 ± 6.1, and positive UPOINT domain number 2.4 ± 0.9. The distribution of each positive domain was 67.2% for urinary, 15.5% for psychosocial, 75.8% for organ-specific, 3.4% for infection, 5.1% for neurological/systemic conditions, and 75.8% for tenderness. Although the mean CPSI total scores tended to increase with an increasing number of positive UPOINT domains, a significant correlation was not observed (r = 0.134, p = 0.312). The sexual dysfunction domain was positive in 62.0% of the cases, but the correlation could not be improved. Conclusions: Urinary, organ specific, and tenderness domains were mainly observed in patients with CP/CPPS. When patients with moderate or grater CPSI scores are clinically evaluated, clinicians should recognize that the UPOINT-positive domain and CPSI score are clinically and pathologically different concepts. (250 words).